Education and Social Dynamics from Ibn Khaldun's Perspective: A Critical Review and Relevance for the Modern World - Ega Putri Handayani; Muhammad Zalnur; Fauza Masyudi (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
This article Ibn Khaldun’s thoughts on education, evaluation, and social dynamics, as well as their relevance in the modern world. The approach used is a literature review with critical analysis of works discussing Ibn Khaldun’s key consepts. The study’s findings indicate that, according to Ibn Khaldun, education encompasses not only formal teaching but also the moral, social, and spiritual development of individuals. He emphasizes the importance of a gradual teaching method, interactive dialogue, and direct experience in the learning process. Evaluation, in Ibn Khaldun’s view, is closely related to learning outcomes. Proper evaluation enables comprehensive measurement of learning achievements, inckuding intellectual, moral, and social aspects, this process involves continuous assessment that fosters character development and individual competence. In the social domain, Ibn Khaldun’s theory of asabiyyah or social solidarity highlights the importance of unity in creating a stable and civilized society. This concept remains relevant in addressing the challenges of globalization and modern individualism. Although his ideas did not cover aspects of technology and globalization, the values he proposed can serve as a foundation for building a holistic and adaptive educational system. The article concludes that Ibn Khaldun’s thouhts have the potential to enrich contemporary theories of education and social development.